Surat (Abasa): A phonemic approach - Yafeai, Asma; Bettahar , Benissa (Al-Adab Journal, 2024)
This research is an analytical study of Surah (Abasa) in the phonetic rhythm, and it aims to reveal the multiple phonetic phenomena in the surah, and to clarify its semantics and linguistic functions. The internal rhythm that includes all kinds of repetition, the Qur’anic comma, and the implications that follow. The descriptive-analytical approach was chosen to study this sound level, which is important in understanding this miraculous Qur’anic text. The most notable result is that phonetic phenomena contributed to the linguistic construction of the surah, and performed semantic and aesthetic functions appropriate to the context.